EMPOWERing Patients With Diabetes Using Profiling and Targeted Feedbacks Delivered Through Smartphone App and Wearable (EMPOWER): Protocol for a Randomized Controlled Trial on Effectiveness and Implementation - Kwan, Yu Heng; Yoon, Sungwon; Tan, Chuen Seng; Tai, Bee Choo; Tan, Wee Boon; Phang, Jie Kie; Tan, Ngiap Chuan; Tan, Cynthia Yan Ling; Quah, Yan Ling; Koot, David; Teo, Hock Hai; Low, Lian Leng (Frontiers in Public Health, 2022)
Introduction Type 2 diabetes mellitus (T2DM) poses huge burden and cost on the healthcare system. Mobile health (mHealth) interventions that incorporate wearables may be able to improve diabetes self-management. The aim of this randomized controlled trial (RCT) is to demonstrate the clinical and cost-effectiveness of personalized educational and behavioural interventions delivered through an EMPOWER mobile application (app) among patients with T2DM. Methods This is a parallel two-arm randomized controlled trial (RCT). Patients with T2DM recruited from primary care will be randomly allocated in a 1:1 ratio to either intervention or control group. The intervention group will receive personalized educational and behavioural interventions through the EMPOWER app in addition to their usual clinical care. The control group will receive the usual clinical care for their T2DM but will not have access to the EMPOWER app. Our primary outcome is patient activation score at 12 months. Secondary outcomes will include HbA1c, physical activity level and diet throughout 12 months; quality of life (QoL), medication adherence, direct healthcare cost and indirect healthcare cost at 6 months and 12 months. Discussion This RCT will provide valuable insights into the implementation of personalized educational and behavioural interventions delivered through mobile application in T2DM management. Findings from this study can help to achieve sustainable and cost-effective behavioural change in patients with T2DM, and this can be potentially scaled to other chronic diseases such as hypertension and dyslipidemia. Trial registration This study was registered on clintrials.gov on the August 19, 2020, under the trial registration number: NCT04518566